Formation of groundwater levels of drained lands in the natural and climatic conditions of the Novgorod region - O. V. Balun; E. P. Shkodina; V. A. Yakovleva; S. Yu. Zhukova (Аграрная наука Евро-Северо-Востока, 2023)
Studies on the formation of groundwater levels have been carried out on open and closed drainage systems in the natural and climatic conditions of the Novgorod region for more than 30 years at 2 pilot production sites. On the first site there are 4 structures of closed drainage: shallow with a depth of 70 cm; medium-deep drainage (drainage depth 110 cm) with various options for filling the drainage trench-wood chips and sand-gravel mixture; two-tier drainage (drainage depth 110 and 60 cm). On the second site there are four open drainage structures: channels; hollows – without hydro-reclamation structures; with drainage along the bottom-tubular and strip-free. The average long-term data on groundwater regimes on experimental structures were obtained and conclusions were drawn that the average seasonal groundwater level formed by closed drainage systems is 18 cm lower compared to open drainage systems; the most favorable groundwater regime is formed by drainage systems of two-tier drainage. The dependences of groundwater levels formed during the most intense periods of operation of drainage systems (May – 1st decade of June) on the amount of precipitation for previous periods are analyzed. It was revealed that the closeness of the relationship between groundwater levels and the amount of precipitation in the open drainage variants is less close (r2 = 0.01-0.30) compared with the closed drainage variants (r2 = 0.02-0.54). The closest relationship on closed drainage systems is observed between the groundwater level of the third decade of May and precipitation for May: during this period, with an increase in precipitation by 1 mm, groundwater rises by 0.3 cm – in the variant with chip filling and by 0.6 cm – in the variants of shallow and two-tier drainage.